Circular RNA circFNDC3AL Upregulates BCL9 Expression to Promote Chicken Skeletal Muscle Satellite Cells Proliferation and Differentiation by Binding to miR-204 - Wei, Yuanhang; Tian, Yongtong; Li, Xinyan; Amevor, Felix Kwame; Shen, Xiaoxu; Zhao, Jing; Zhao, Xiyu; Zhang, Xinyi; Huang, Wenling; Hu, Jihong; Yi, Jie; Yan, Lei; et al. (Frontiers in Cell and Developmental Biology, 2021)
Skeletal muscle is a heterogeneous tissue that is essential for initiating movement and maintaining homeostasis. The genesis of skeletal muscle is an integrative process that lasts from embryonic development to postnatal stages, which is carried out under the modulation of many factors. Recent studies have shown that circular RNAs (circRNAs), a class of non-coding RNAs, are involved in myogenesis. However, more circRNAs and their mechanisms that may regulate skeletal muscle development remain to be explored. Through in-depth analysis of our previous RNA-Seq data, circFNDC3AL was found to be a potentially functional circRNA highly expressed during embryonic development of chicken skeletal muscle. Therefore, in this study, we investigated the effect of circFNDC3AL on skeletal muscle development in chickens and found that circFNDC3AL promoted chicken skeletal muscle satellite cell (SMSC) proliferation and differentiation. To gain a thorough understanding of the exact modulatory mechanisms of circFNDC3AL in chicken skeletal muscle development, we performed target miRNA analysis of circFNDC3AL and found that circFNDC3AL has a binding site for miR-204. Subsequently, we demonstrated that miR-204 inhibited chicken SMSC proliferation and differentiation, which showed the opposite functions of circFNDC3AL. Furthermore, we identified the miR-204 target gene BCL9 and validated that miR-204 had an inhibitory effect on BCL9, while the negative effect could be relieved by circFNDC3AL. In addition, we verified that BCL9 performed the same positive functions on chicken SMSC proliferation and differentiation as circFNDC3AL, as opposed to miR-204. In conclusion, our study identified a circRNA circFNDC3AL that upregulates BCL9 expression to promote the proliferation and differentiation of chicken SMSCs by binding to miR-204.